Hepatocyte Growth Factor-Dependent Antiviral Activity of Activated cdc42-Associated Kinase 1 Against Hepatitis B Virus - Lee, Hye Won; Choi, Yongwook; Lee, Ah Ram; Yoon, Cheol-Hee; Kim, Kyun-Hwan; Choi, Byeong-Sun; Park, Yong Kwang (Frontiers in Microbiology, 2021)
Activated cdc42-associated kinase 1 (ACK1) is a well-known non-receptor tyrosine kinase that regulates cell proliferation and growth through activation of cellular signaling pathways, including mitogen-activated protein kinase (MAPK). However, the anti-HBV activity of ACK1 has not been elucidated. This study aimed to investigate the role of ACK1 in the HBV life cycle and the mechanism underlying the anti-HBV activity of ACK1. To examine the antiviral activity of ACK1, we established HepG2-ACK1 cells stably overexpressing ACK1. The HBV life cycle, including HBeAg/HBsAg secretion, HBV DNA/transcription, and enhancer activity, was analyzed in HepG2 and HepG2-ACK1 cells with HBV replication-competent HBV 1.2mer (HBV 1.2). Finally, the anti-HBV activity of ACK1 was examined in an HBV infection system. ACK1 suppressed HBV gene expression and transcription in HepG2 and HepG2-ACK1 cells. Furthermore, ACK1 inhibited HBV replication by decreasing viral enhancer activity. ACK1 exhibited its anti-HBV activity via activation of Erk1/2, which consequently downregulated the expression of HNF4α binding to HBV enhancers. Furthermore, hepatocyte growth factor (HGF) induced ACK1 expression at an early stage. Finally, ACK1 mediated the antiviral effect of HGF in the HBV infection system. These results indicated that ACK1 induced by HGF inhibited HBV replication at the transcriptional level by activating the MAPK-HNF signaling pathway. Our findings suggest that ACK1 is a potentially novel upstream molecule of MAPK-mediated anti-HBV activity.